Molecular typing of Candida albicans isolated from oral cavity of cancer patients using randomly amplified polymorphic DNA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
To facilitate studies on the epidemiology of Candida, numerous phenotypic and genotypic typing systems have been developed. The polymerase chain reaction (PCR) can be adapted for pringerprinting microorganisms by using paired primers derived from previously characterized sequences for PCR amplification. The aim of the present study was to develop and use Randomly Amplified Polymorphic DNA (RAPD) for molecular genetic typing of Candida albicans. RAPD which is based on PCR with arbitrary short primers, was used to evaluate a panel of 9 Candida albicans that were isolated from oral cavity of cancer patients in Yogyakarta. Analysis of RAPDs with primer AT (5' GCGCACGG 3') gave 5 types of banding patterns. Primer NT (5' CCCTAGGA 3') yielded 8 types of banding patterns. These data indicate that many different substrains of Candida albicans can infect patients with cancer disease causing either oral colonization or oral candidosis. This study indicates that because of its ease and reproducibility, RAPD analysis is useful in providing genotypic characters for confirming the identities of stock isolates, for typing such as Candida albicans, as well as rapid identification of pathogenic fungi.